2016
DOI: 10.1002/jcla.21961
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Detection of Genomic Mutations in gyrA and parC Genes of Escherichia coli by Multiplex Allele Specific Polymerase Chain Reaction

Abstract: MAS-PCR may be used for rapid detection of FR resistance in routine laboratory as well as in epidemiology study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 31 publications
0
12
0
2
Order By: Relevance
“…Screening of E. coli isolates for ARG types was conducted using PCR for each isolate depending on the antibiotic resistance phenotype. The ARGs we examined were (1) carbapenemase genes bla NDM , bla IMP bla KPC , bla VIM , bla OXA , bla AIM , bla BIC , bla DIM , bla GIM , bla SIM , and bla SPM including bla NDM and bla CTX-M subtyping (Poirel et al, 2011), (2) β-lactamase genes bla SHV , bla TEM , and bla CTX-M (Casella et al, 2018), (3) plasmidmediated AmpC β-lactamase genes bla MOX , bla CMY , bla LAT , bla DHA , bla ACC , bla MIR , bla ACT , and bla FOX (Perez-Perez and Hanson, 2002), (4) colistin resistance genes mcr-1-8 (Rebelo et al, 2018;Yang et al, 2018;Carroll et al, 2019), and (5) plasmid-mediated quinolone resistance (PMQR) genes qnrA, qnrB and qnrS including whether the gyrA and parC genes in the quinolone resistance determining region (QRDR) were mutated (Komp et al, 2003;Kraychete et al, 2016;Onseedaeng and Ratthawongjirakul, 2016). PCR primers used for screening are shown in Supplementary Table S1.…”
Section: Arg Detectionmentioning
confidence: 99%
“…Screening of E. coli isolates for ARG types was conducted using PCR for each isolate depending on the antibiotic resistance phenotype. The ARGs we examined were (1) carbapenemase genes bla NDM , bla IMP bla KPC , bla VIM , bla OXA , bla AIM , bla BIC , bla DIM , bla GIM , bla SIM , and bla SPM including bla NDM and bla CTX-M subtyping (Poirel et al, 2011), (2) β-lactamase genes bla SHV , bla TEM , and bla CTX-M (Casella et al, 2018), (3) plasmidmediated AmpC β-lactamase genes bla MOX , bla CMY , bla LAT , bla DHA , bla ACC , bla MIR , bla ACT , and bla FOX (Perez-Perez and Hanson, 2002), (4) colistin resistance genes mcr-1-8 (Rebelo et al, 2018;Yang et al, 2018;Carroll et al, 2019), and (5) plasmid-mediated quinolone resistance (PMQR) genes qnrA, qnrB and qnrS including whether the gyrA and parC genes in the quinolone resistance determining region (QRDR) were mutated (Komp et al, 2003;Kraychete et al, 2016;Onseedaeng and Ratthawongjirakul, 2016). PCR primers used for screening are shown in Supplementary Table S1.…”
Section: Arg Detectionmentioning
confidence: 99%
“…It can be assumed that this, as a universally functional mechanism, is likely to affect DNA supercoiling, and the expression of several virulence factors and proteins as described in different species is the same ( Ozeki et al., 1997 ; Aubry et al., 2006 ; Abdelbaqi et al., 2007 ; Hashimi et al., 2008 ; Lau et al., 2011 ; Malik et al., 2012 ; Yamachika et al., 2012 ; Sutera et al., 2017 ). Ciprofloxacin resistance usually occurs due to specific point mutations within the DNA gyrase A ( gyrA) and/or topoisomerase IV parC and parE genes, often in combination ( Casin et al., 2003 ; Johnning et al., 2015 ; Onseedaeng and Ratthawongjirakul, 2016 ). Annotation of mutation in the gyrase A gene is considered not to be sufficient to produce resistance to ciprofloxacin ( Hooper and Jacoby, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Since AS-PCR was first reported in 1989 (Newton et al, 1989), it has been widely used to screen single nucleotide polymorphisms and mutations. Although AS-PCR is considered as low specificity and sensitivity (Sharma et al, 2016), Onseedaeng & Ratthawongjirakul (2016) identified mutations of the gyrA and parC gene in Escherichia coli with high sensitivity and specificity by using AS-PCR. Due to its simple operation, low cost, and relatively high specificity and sensitivity, we successfully used AS-PCR to screen 16 mutations in four first-line DR-genes.…”
Section: Discussionmentioning
confidence: 99%